Potential of solar radiation and wind speed for photovoltaic and wind power hybrid generation in Perlis, Northern Malaysia - Ismail, Daut, Prof. Dr.; Muhammad Irwanto, Misrun; Mohd Irwan, Yusoff; Gomesh Nair, Shasidharan; Rosnazri, Ali; Noor Syafawati, Ahmad (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/